2017
DOI: 10.1002/srin.201700022
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Strain Rate Sensitivity of Strain‐induced Martensitic Transformation in SUS304 by Real‐time Measurement of Relative Magnetic Permeability

Abstract: With excellent mechanical properties because of strain-induced martensitic transformation (SIMT), applications of austenitic stainless steels can be extended to a further broad range of engineering fields. In order to discover applications from a clarification of their mechanical properties, especially at higher deformation rate, it is important to evaluate an amount of martensite, which can control such excellent performances of the steels during deformation. However, until now, it is quite hard to find exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In situ quantitative measurements based on the AC/DC magnetic permeability measurement techniques result in continuous measurement of phase fraction of austenite during deformation. [38][39][40]75] In the following sections, the basis of various techniques for quantitative assessment of austenite (as listed in Figure 1) during the deformation of TRIP/TRIP-assisted steels will be discussed. Each of these techniques is critically assessed based on their ease of use and accurate measurement of phase fraction and transformation kinetics in TRIP steels.…”
Section: Techniques For the Quantification Of Austenitementioning
confidence: 99%
“…In situ quantitative measurements based on the AC/DC magnetic permeability measurement techniques result in continuous measurement of phase fraction of austenite during deformation. [38][39][40]75] In the following sections, the basis of various techniques for quantitative assessment of austenite (as listed in Figure 1) during the deformation of TRIP/TRIP-assisted steels will be discussed. Each of these techniques is critically assessed based on their ease of use and accurate measurement of phase fraction and transformation kinetics in TRIP steels.…”
Section: Techniques For the Quantification Of Austenitementioning
confidence: 99%
“…For example, Silva et al showed an exponential correlation between martensite volume fraction and phase angle [4] and Khan et al between coil impedance, impedance phase, and martensite content. [22] Compared with the method developed by Cao et al , [19] which was designed for tensile samples, it is already known in many ways that eddy current sensors can be integrated into production processes. [24,25] To be able to perform defined, production-integrated subsurface hardening, the influence of two cutting parameters, namely temperature and feed, on the DIMT was analyzed in the present study.…”
Section: Doi: 101002/srin202000299mentioning
confidence: 99%
“…[ 23 ] One way to determine the DIMT behavior of steel is the nondestructive determination of the relative magnetic permeability by eliminating the influence of the jigs, which was done by Cao et al using DC voltage instead of AC voltage. [ 14,19 ] Another possibility to achieve more accurate results is to use eddy current testing as the excitation frequency can be varied and different studies demonstrate a good correlation between the martensite content and measured values in eddy current testing. For example, Silva et al showed an exponential correlation between martensite volume fraction and phase angle [ 4 ] and Khan et al between coil impedance, impedance phase, and martensite content.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations